Evaluating the effects of increased protein intake on muscle strength, hypertrophy and power adaptations with concurrent training: a narrative review - Camera, M. D. (Sports Medicine, 2022)
Concurrent training incorporates dual exercise modalities, typically resistance and aerobic-based exercise, either in a single session or as part of a periodized training program, that can promote muscle strength, mass, power/force and aerobic capacity adaptations for the purposes of sports performance or general health/wellbeing. Despite multiple health and exercise performance-related benefits, diminished muscle hypertrophy, strength and power have been reported with concurrent training compared to resistance training in isolation. Dietary protein is well-established to facilitate skeletal muscle growth, repair and regeneration during recovery from exercise. The degree to which increased protein intake can amplify adaptation responses with resistance exercise, and to a lesser extent aerobic exercise, has been highly studied. In contrast, much less focus has been directed toward the capacity for protein to enhance anabolic and metabolic responses with divergent contractile stimuli inherent to concurrent training and potentially negate interference in muscle strength, power and hypertrophy. This review consolidates available literature investigating increased protein intake on rates of muscle protein synthesis, hypertrophy, strength and force/power adaptations following acute and chronic concurrent training. Acute concurrent exercise studies provide evidence for the significant stimulation of myofibrillar protein synthesis with protein compared to placebo ingestion. High protein intake can also augment increases in lean mass with chronic concurrent training, although these increases do not appear to translate into further improvements in strength adaptations. Similarly, the available evidence indicates protein intake twice the recommended intake and beyond does not rescue decrements in selective aspects of muscle force and power production with concurrent training.